High risk men who have sex with men in Spain are reporting low intentions of actively seeking HIV testing: results from a cross-sectional study - Juan Hoyos; Kostas Koutentakis; Tomás Maté; Jose Pulido; Luis Sordo; Juan-Miguel Guerras; María-José Belza (BMC, 2020)
Abstract Background We analyse unprotected anal intercourses (UAI) self-reported by a sample of men who have sex with men (MSM), by their future testing intentions and past testing history to identify undertested subpopulations that could be contributing to onward transmission. Methods We recruited MSM through gay dating websites in Spain from September 2012 to April 2013. For MSM at risk of acquiring or unknowingly transmitting HIV (at risk hereafter) we calculate time at risk, number of UAI in the last 12 months and last 5 years by testing intention (low intention (LI), Medium intention (MI), high intention (HI)) and past testing history. For never testers we analyse the reasons for not having been tested. Results Of 3272 MSM at risk, 19.8% reported LI of testing. MSM with LI reported the longest period at risk (8.49 years (p < 0.001)) and reported 3.20 UAI/person in the last 12 months (vs. 3.23 and 2.56 in MSM with HI and MI (p < 0.001)) and 12.90 UAI/person in the last 5 years (vs. 8.07 and 9.82 in MSM with HI and MI (p < 0.001)). Those with LI accounted for 21 and 27% of all the UA acts occurring in the last 12 months and the last 5 years. Among never testers (40.6%), those with LI reported lower risk perception (p = 0.006). Conclusion We identified a group of high risk and undertested MSM that could be behind a substantial proportion of the UAIs with potential of transmission/acquisition of HIV. Given their low willingness to seek an HIV test and low risk perception, they constitute a population that will probably require approaches other than client initiated strategies.